Implications of flavonoids as potential modulators of cancer neovascularity - Liskova, Alena; Koklesova, Lenka; Samec, Marek; Varghese, Elizabeth; Abotaleb, Mariam; Samuel, Samson Mathews; Smejkal, Karel; Biringer, Kamil; Petras, Martin; Blahutova, Dana; Bugos, Ondrej; Pec, Martin; et al. (Journal of cancer research and clinical oncology, 2020)
PURPOSE: The formation of new blood vessels from previous ones, angiogenesis, is critical in tissue repair, expansion or remodeling in physiological processes and in various pathologies including cancer. Despite that, the development of anti-angiogenic drugs has great potential as the treatment of cancer faces many problems such as development of the resistance to treatment or an improperly selected therapy approach. An evaluation of predictive markers in personalized medicine could significantly improve treatment outcomes in many patients. METHODS: This comprehensive review emphasizes the anticancer potential of flavonoids mediated by their anti-angiogenic efficacy evaluated in current preclinical and clinical cancer research. RESULTS AND CONCLUSION: Flavonoids are important groups of phytochemicals present in common diet. Flavonoids show significant anticancer effects. The anti-angiogenic effects of flavonoids are currently a widely discussed topic of preclinical cancer research. Flavonoids are able to regulate the process of tumor angiogenesis through modulation of signaling molecules such as VEGF, MMPs, ILs, HIF or others. However, the evaluation of the anti-angiogenic potential of flavonoids within the clinical studies is not frequently discussed and is still of significant scientific interest.
Keywords: flavonoidy; Vascular Endothelial Growth Factor A; Cancer; signální transdukce; Flavonoids; Signal Transduction; inhibitory angiogeneze; VEGF; Humans; Anti-cancer therapy; Tumor angiogenesis; Matrix Metalloproteinases; lidé; Neovascularization, Pathologic; matrixové metaloproteinasy; vaskulární endoteliální růstový faktor A; interleukiny; Angiogenesis Inhibitors; Neoplasms; nádory; Neovascularity; Interleukins; patologická angiogeneze